Life cycle study of maize stem borer (Chilo partellus Swinhoe) under laboratory condition at National Maize Research Program, Rampur, Chitwan, Nepal - Neupane, Saraswati; Subedi, Subash (Journal of Agriculture and Natural Resources, 2019)
Maize stem borer (Chilo partellus swinhoe) is one of the major threatening global pests of maize and considered as the national top priority entomological research problem in Nepal. The Life cycle of maize stem borer was studied under laboratory condition at National Maize Research Program (NMRP), Rampur, Chitwan, Nepal during 2018. Development of stem borer undergoes following stages like egg, larvae, pupa and adult. Eggs and different instars of maize stem borer larvae were collected from maize fields were put with host materials (maize leaf and stem) to become different instars of larva, pupae and finally turned to adults. Eggs were harvested from adults and kept on blotting paper which was kept inside petriplates and reared for adults. Their life span in each stage (egg, larva and pupa) and the fecundity of adults recorded. Daily room temperature and relative humidity (RH) in laboratory conditions were recorded. The Egg incubation period ranged from 4-7 days and hatched generally in the early morning (6-8 AM). The complete larvae period ranged from 29 to 36 days while pupal period was ranged from 7 to 12 days. The average male pupal length was found 13 mm and female was 16 mm long. The fecundity of C. partellus Swinhoe was recorded 150-160 eggs per female. The Oviposition period was  4 days and adult male survived for 4-7 days while female for 4-9 days. The average life cycle of C. partellus completed in (44-48) days during summer whereas (60-64) days during winter at average room temperature of (26-27° C) and RH of (70-80%). These results have important implications to know the survival and development of pest including effective pest management strategy.